2021
DOI: 10.1111/jgs.17280
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine disparities during COVID‐19: Provider offering and individual technology availability

Abstract: 4. Covid-19 data. Tracking covid-19 excess deaths across countries. https://www.economist.com/graphic-detail/coronavirusexcess-deaths-tracker (accessed February 11, 2021). 5. Mejoramiento de la vigilancia de mortalidad por COVID-19 en América Latina y el Caribe mediante la vigilancia de mortalidad por todas las causas. Documento de orientación. Mayo 25, 2020. https://www.paho.org/es/documentos/mejorar-vigilanciamortalidad-por-covid-19-america-latina-caribe-mediante-vigilancia (accessed January 22, 2021). 6. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…Race and ethnicity was a significant factor for all three outcomes, with Black Non-Hispanic Medicare enrollees being less likely to be offered telehealth services during the COVID-19 pandemic, more likely to be offered telehealth services before the COVID-19 pandemic, and more likely to use telehealth services during COVID-19 compared to White Non-Hispanic enrollees. These results may seem contradictory; however, they support previous research that shows that telehealth services were available to Black Non-Hispanic Medicare enrollees at higher rates than to White Non-Hispanic enrollees before COVID-19, but that during the COVID-19 pandemic, telehealth coverage subsequently increased the most for White Non-Hispanic enrollees and increased the least for Black Non-Hispanic enrollees, leading to a disparity in telehealth coverage ( 26 ). Previous research also shows that, despite telehealth services being less available to them during COVID-19, Black Medicare enrollees were more likely to use telehealth services during COVID-19 than White enrollees ( 12 ), while other research shows that Black patients were more likely to use audio-only telehealth services compared to video visits during COVID-19 ( 27 ).…”
Section: Discussionsupporting
confidence: 61%
“…Race and ethnicity was a significant factor for all three outcomes, with Black Non-Hispanic Medicare enrollees being less likely to be offered telehealth services during the COVID-19 pandemic, more likely to be offered telehealth services before the COVID-19 pandemic, and more likely to use telehealth services during COVID-19 compared to White Non-Hispanic enrollees. These results may seem contradictory; however, they support previous research that shows that telehealth services were available to Black Non-Hispanic Medicare enrollees at higher rates than to White Non-Hispanic enrollees before COVID-19, but that during the COVID-19 pandemic, telehealth coverage subsequently increased the most for White Non-Hispanic enrollees and increased the least for Black Non-Hispanic enrollees, leading to a disparity in telehealth coverage ( 26 ). Previous research also shows that, despite telehealth services being less available to them during COVID-19, Black Medicare enrollees were more likely to use telehealth services during COVID-19 than White enrollees ( 12 ), while other research shows that Black patients were more likely to use audio-only telehealth services compared to video visits during COVID-19 ( 27 ).…”
Section: Discussionsupporting
confidence: 61%
“…14 A study of telemedicine technologies among Medicare beneficiaries revealed that compared with other racial groups, Black patients experienced the lowest rate of increase in telemedicine availability during the pandemic. 15 Our study provides insights on inequities in telemedicine visit uptake among patients with different hematologic cancers receiving diverse types of treatments across various geographic regions in US during the critical time of early pandemic.…”
Section: Discussionmentioning
confidence: 95%
“…In a racially diverse study of US older adults, 76% reported minimal video-based socializing; access to and discomfort with technology were described as a key barrier to coping, maintaining social connection, and accessing health care during the pandemic [ 26 ]. There are other factors that are associated with nonuse of digital technologies that we did not evaluate, including cognitive impairment, frailty, vision or hearing impairments, and non-English/French speaking ability [ 27 , 28 ]. The unique needs and barriers of these population subgroups warrant thorough investigation and consideration when designing interventions, programs, and services.…”
Section: Discussionmentioning
confidence: 99%